2004
DOI: 10.1097/01.tp.0000116562.15920.43
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience With Alemtuzumab (Campath-1h) and Low-Dose Tacrolimus Immunosuppression in Adult Liver Transplantation

Abstract: C1H and low-dose Tac seems to be at least as effective as our standard Tac and steroids regimen in preventing acute rejection in adult liver allotransplantation with less renal toxicity and less use of maintenance steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 14 publications
3
53
0
3
Order By: Relevance
“…More recently alemtuzumab has been used increasingly in the United State as an induction agent for kidney, pancreas, lung and liver transplantation, again with promising short-term results (18)(19)(20). To date there has been no prospective, randomized controlled trial of alemtuzumab in transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently alemtuzumab has been used increasingly in the United State as an induction agent for kidney, pancreas, lung and liver transplantation, again with promising short-term results (18)(19)(20). To date there has been no prospective, randomized controlled trial of alemtuzumab in transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in renal transplant patients have shown its efficacy in preventing rejection when used in combination with low-dose CNIs or sirolimus [99101] . Tzakis et al [102] compared the use of alemtuzumab induction therapy combined with lowdose tacrolimus in liver transplant recipients receiving standard doses of tacrolimus and corticosteroids. Although patients who received alemtuzumab had less renal dysfunction and acute rejection in the first two months post-transplant, the overall incidence of rejection was not significantly different between the two groups.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Parece, por tanto, que con esta pauta se podrían mantener los injertos con bajas dosis de inmunodepresión, con pocos efectos secundarios y a un coste bajo. La experiencia en el TH ha sido publicada recientemente por Tzakis et al 63 y Marcos et al 64 .…”
Section: Nuevas Pautas De Inmunodepresión Inductoras De Toleranciaunclassified